Changes in Oxidative Stress and Antioxidant Status in Streptozotocin-Induced Diabetic Wistar Albino Rats: Effects of Oral Zinc Supplementation: Oxidative stress and antioxidant status in diabetic rats: Impact of oral zinc supplementation - Boukadoum, Ali; Tbahriti, Hadja Fatima (Iranian Journal of Pharmaceutical Sciences, 2024)
A major factor in the development and course of diabetes mellitus is oxidative stress. Overproduction of reactive oxygen species in the presence of concurrent deficient antioxidant mechanisms leads to enhanced oxidative stress. The objective of the current study was to assess the effect of zinc supplementation on oxidative stress and total antioxidant capacity in streptozotocin induced diabetic rats. Thirty-two male Wistar albino rats were randomly divided into four equal groups: Group 1- the untreated control; group 2- the zinc-supplemented group; Group 3- the diabetic-STZ-induced group; and Group 4- the diabetic-STZ-induced group supplemented with zinc. A single intraperitoneal injection of streptozotocin (55 mg/kg body weight) was used to induce diabetes. All procedures and animal handling procedures were performed according to the Institutional Animal Care and Use Committee. Zinc sulfate was administered via gavage at a dose of 100 mg/kg body weight for 60 days. On the last day of the experiment, the rats were sacrificed under anaesthesia. Protein carbonyl (PC), total antioxidant capacity (TAC), thiobarbituric acid reactive substances (TBARS), and enzyme activities such as those of catalase (CAT) and superoxide dismutase (SOD) were measured in plasma. Comparisons between groups were performed using analysis of variance (ANOVA) for normally distributed variables or Bartlett’s test for inequality of population variances. Differences were considered significant at P<0.05. Zinc supplementation leads to an increase in the total serum proteins of the antioxidant defense system, and the activities of CAT, SOD and TAC increase. On the other hand, the content of TBARS decreased and the concentration of PC decreased. Zinc supplementation has been shown to have positive effects on antioxidant capacity and glycemic control in diabetic rats. In conclusion, the results of this study demonstrate the beneficial effect of zinc supplementation on oxidative stress in diabetic rats.